Communal Conflicts in Benue and the Herdsmen Conundrums - Ajiye, Sam Olatunji (Advances in Social Sciences Research Journal, 2019)
The communal conflict between the nomadic herdsmen from northern Nigeria and the agrarian communities of Benue has escalated in recent times and is spreading across boundaries, threatening the country’s security and stability. The activities of the Fulani herdsmen started surreptitiously in Benue State over two decades ago. Approximately 2,500 people lost their lives in 2016 because successive governments neglected the conflict and its victims, and where action was taken, it was insufficient. Consequently, the continual mayhem unleashed by the herdsmen signifies persecution because it was targeted at a particular religious group, and the destruction of their worship centers. Also, the continual violence and the lukewarm attitude of the central government is suggestive of a deliberate agenda, championed by the Fulani herdsmen, to occupy an area considered as being dominated by one ethno-religious group. Familiar problems – relating to land and water use, obstruction of traditional migration routes, livestock theft and crop damage – tend to trigger these disputes. But their roots run deeper. Drought and desertification have degraded pastures, dried up many natural water sources across Nigeria’s far-northern Sahelian belt and forced large numbers of herders to migrate south in search of grassland and water for their herds. Herders migrating into the savannah and rain forests of the north central states are moving into regions where high population growth over the last four decades has heightened pressure on farmland, increasing the frequency of disputes over crop damage, water pollution and cattle rustling. In the absence of mutually accepted mediation mechanisms, these disagreements increasingly turn violent. Majority of Christian communities resent the influx of predominantly Muslim herders, portrayed in some narratives as an “Islamization force’’. Herders are predominantly Fulani, lending an ethnic dimension to strife. This research provides an analysis of the violent conflict in Benue state where most of the victims are Christians. The study critically examines the root causes of the conflict taking into account the nature of abuse targeted at women and children. The research adopted the use of Timeline as analytical tool and concludes that the Fulanis are psychologically conditioned through a cultural practice of revenge. Hence, the urgent need for cultural de-radicalizations and mind healing of the herders, amongst other recommendations.